CRIMINAL JUVENILE LIABILITIES UNDER INDONESIAN LAWS AND THE 1989 UNITED NATIONS CONVENTION ON THE RIGHTS OF THE CHILD: AN ANALYSIS - Khairunnisa, Dwi; Mahfud, Mahfud (Universitas Syiah Kuala, 2023)
This study evaluates the alignment between criminal responsibilities imposed on juvenile offenders in Indonesia and the United Nations Convention on the Rights of the Child (UNCRC). Specifically, it focuses on the Indonesian Law Number 11 of 2012 on Juvenile Criminal Justice System, which was enacted in accordance with the UNCRC. Through the use of normative methods, this study reveals that there are existing challenges hindering the effective implementation of the UNCRC provisions. Notably, the issue of long-term juvenile detention arises as a significant concern, as it restricts the autonomy and freedom of these individuals. The UNCRC emphasizes that custody should only be utilized as a last resort for young offenders. Therefore, it is crucial for the Indonesian justice system to establish more efficient and effective laws that discourage the imprisonment of juvenile criminals, thereby upholding the principles enshrined in the UNCRC.